Treatment outcome of acne vulgaris with topical application of clindamycin gel and benzoyl peroxide gel as supplementary files - Parmar, Devendra; Salvi, Dhairya (International Journal of Research in Dermatology, 2019)
Background: Acne vulgaris is one of the commonest inflammatory skin disorders. It also has a psychosocial impact on patients, specially known in adolescents and hence needs effective treatment. The objectives of the study was to find out and ascertain different clinical presentations of acne vulgaris in both sexes of various age groups and to find out the outcome of treatment with various topical modalities in various clinical types. Methods: A total of 150 patients with acne vulgaris were studied with age group >10 years. Detailed history, thorough physical examination and relevant investigations were done. Patients were divided into 2 groups of 75 each and each group received different treatment and were followed up at 4th, 8th and 12th week. Results: At the end of 12 weeks there was significant improvement in grade-II patients treated with cindamycin 1% gel. Conclusions: The results of the study show that different grades of acne vulgaris respond with different regimens.